Use of eco-mapping in health services research: a scoping review protocol - Hardeep Singh; Michelle L A Nelson; Terence Tang; Marianne Saragosa; Carolyn Steele Gray; Ani Orchanian-Cheff (BMJ Open, 2023)
Introduction People with complex health and social needs often require care from different providers and services. Identifying their existing sources of support could assist with addressing potential gaps and opportunities for enhanced service delivery. Eco-mapping is an approach used to visually capture people’s social relationships and their linkages to the larger social systems. As it is an emerging and promising approach in the health services field, a scoping review on eco-mapping is warranted. This scoping review aims to synthesise the empirical literature that has focused on the application of eco-mapping by describing characteristics, populations, methodological approaches and other features of eco-mapping in health services research.Methods and analysis This scoping review will follow the Joanna Briggs Institute methodology. From the date of database construction to 16 January 2023, the following databases in English will be searched: Ovid Medline, Ovid Embase, CINAHL Ultimate (EBSCOhost), Emcare (Ovid), Cochrane Central Register of Controlled Trials (Ovid) and Cochrane Database of Systematic Reviews (Ovid) Study/Source of Evidence selection. The inclusion criteria consist of empirical literature that uses eco-mapping or a related tool in the context of health services research. Two researchers will independently screen references against inclusion and exclusion criteria using Covidence software. Once screened, the data will be extracted and organised according to the following research questions: (1) What research questions and phenomena of interest do researchers address when using eco-mapping? (2) What are the characteristics of studies that use eco-mapping in health services research? (3) What are the methodological considerations for eco-mapping in health services research?Ethics and dissemination This scoping review does not require ethical approval. The findings will be disseminated through publications, conference presentations and stakeholder meetings.Trial registration number https://doi.org/10.17605/OSF.IO/GAWYN.